Melbourne colorectal collaboration: a multicentre review of the impact of COVID‐19 on colorectal cancer in Melbourne, Australia. Issue 5 (8th April 2022) - Chen, Michelle Zhiyun; Tay, Yeng Kwang; Teoh, Wiliam MK; Kong, Joseph CH; Carne, Peter; D'Souza, Basil; Chandra, Raaj; Bui, Andrew; ,
Abstract: Background: As coronavirus (COVID‐19) cases continue to rise, healthcare workers have been working overtime to ensure that all patients receive care in a timely manner. Our study aims to identify the impact and outcomes of COVID‐19 on colorectal cancers presentations across the five major colorectal units in Melbourne, Australia. Methods: This is a retrospective study from a prospectively collected database from the binational colorectal cancer audit (BCCA) registry, as well as inpatient records. All patients with colorectal cancer between Pre‐COVID‐19 period (1 July 2018–2030 June 2019) and COVID‐19 period (1 July 2020–2030 June 2021) were compared. Benign pathology and other cancer types were excluded. Results: A total of 1609 patients were included in the study (700 Pre‐COVID‐19 period, 906 COVID‐19 period). During COVID‐19 period, there was a higher proportion of emergency surgery (28.1% vs. 19.8%; P < 0.001), a higher nodal ( P = 0.024) and metastatic stage ( P = 0.018) at presentation, but no increase in the rate of return to operating theatres ( P = 0.240), inpatient death ( P = 0.019) or 30‐day readmission ( P = 0.000). There was also no difference in the post‐operative surgical complications ( P = 0.118). Utility of neoadjuvant therapy did not increase during the pandemic ( P = 0.613). Conclusion: The heightened measures in the healthcare system ensured CRC patients still received their surgery in a timely fashion. With the current rise in the new strain of COVID‐19 (Omicron), we have to continue to come up with new strategies to provide timely access to CRC care. Abstract : Colorectal cancer before and during COVID‐19 pandemic.